HUBUNGAN ANTARA MOTIVASI BELAJAR DAN HASIL BELAJAR BAHASA ARAB MAHASISWA FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Syahruddin Usman Usman (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2015)
Abstract: This research discussed about the relationship between learning motivation and Arabic learning outcomes of the students at the Arabic Education Department, faculty of education and teaching science of UIN Alauddin Makassar. This research aimed at obtaining a description of the level of learning motivation and Arabic learning outcomes as well as the relationship between learning motivation and Arabic learning outcomes of students at the Arabic education. The research location was at the faculty of education and teaching science of UIN Alauddin Makassar. The research type was correlational with quantitative approach. The population was all students of the first semester of arabic education department in academic year 2014 that consists of 110 students, and only 45 students was taken as the sample. The research instruments were a questionnaires and a test. The data analysis technique used was descriptive and infrensial statistics. The results of the research sH0wed that (1) The students’ learning outcomes in Arabic in general were in the moderate category, (2) The students’ learning motivation in general were in the high category, (3) there was a significant relationship between learning motivation and students’ learning outcomes in Arabic because the score of rcount (0,78 was higher than the rtabel (0.294).Abstrak: Penelitian ini membahas tentang hubungan antara motivasi belajar dan hasil belajar bahasa Arab mahasiswa jurusan Pendidikan Bahasa Arab pada Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar. Penelitian ini bertujuan untuk memperoleh gambaran tentang tingkat motivasi belajar bahasa Arab dan hasil belajar bahasa Arab serta hubungan antara motivasi belajar dan hasil belajar bahasa Arab mahasiswa jurusan Pendidikan Bahasa Arab pada Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar. Lokasi penelitian  Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar. Jenis penelitian ini termasuk penelitian korelasional, pendekatannya kuantitaif. Populasinya adalah seluruh mahasiswa semester V jurusan Pendidikan Bahasa Arab tahun 2014 yang berjumlah 110 orang, sampel 45 orang. Instrumennya adalah angket dan butir soal. Teknik analisis data yang digunakan adalah statistik deskriptif dan infrensial. Hasil penelitian menunjukkan bahwa (1) hasil belajar bahasa Arab mahasiswa jurusan Pendidikan Bahasa Arab pada Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar secara umum kategori sedang, (2) motivasi belajar mahasiswa kategori tinggi, dan (3)terdapat hubungan yang signifikan antara motivasi belajar dan hasil belajar bahasa Arab dimana rhitung (0,78) lebih besar dari rtabel (0,294).